Honda Motorcycle Stock Forecasting System Using Double Exponential Smoothing Method (case Study of Honda Dealer PT - Tommy Ferdiansyah; Rifki Fahrial Zainal; Arif Arizal (Fakultas Teknik Universitas Bhayangkara, 2019)
Stock in the warehouse of PT. Delta Sari Agung Sidoarjo is currently unstable, therefore between in and out stock is still out of control. Forecasting is estimating the state of the future through testing the state of the past. In social life, everything is uncertain and difficult to predict accurately, so forecasting is needed. In other words forecasting aims to get forecasting that can minimize forecasting errors (forecast error) which is usually measured by mean square error, mean absolute error, and so on. The Double Exponential Smoothing method is used for forecasting by determining the amount of α (alpha), as well as the smoothing process twice and this study is compared with ANNMatlab. From the results of the comparison of the trial system forecasting and JST-Matlab there is a difference of 16 motorbikes from the remaining stock, which is for the results of forecasting 622 and JST-Matlab 638 results.